Hot Pants at the Border: Sorting Sex Work from Trafficking. (29th October 2013) - Pickering, Sharon; Ham, Julie
Abstract: The role of borders in managing sex work is a valuable site for analysing the relationship between criminal justice and migration administration functions. For the purposes of this article, we are concerned with how generalized concerns around trafficking manifest in specific interactions between immigration officials and women travellers. To this end, this article contributes to a greater understanding of the micro-politics of border control and the various contradictions at work in the everyday performance of the border. It uses an intersectional analysis of the decision making of immigration officers at the border to understand how social differences become conflated with risk, how different social locations amplify what is read as risky sexuality and how sexuality is constructed in migration. What the interviews in our research have demonstrated is that, while the border is a poor site for identifying cases of trafficking into the sex industry, it is a site of significant social sorting where various intersections of intelligence-led profiling and everyday stereotyping of women, sex work and vulnerability play out.